Influenza vaccination hesitancy and its determinants among elderly in China: A national cross-sectional study. Issue 33 (5th August 2022) - Hou, Zhiyuan; Guo, Jia; Lai, Xiaozhen; Zhang, Haijun; Wang, Jiahao; Hu, Simeng; Du, Fanxing; Francis, Mark R.; Fang, Hai
Highlights: Among Chinese elderly, 19% were hesitant to and 18% refused flu vaccination in 2019. Flu vaccine hesitancy was more prevalent among well-educated and urban-dwelling elderly. Only 39% of elderly aware of themselves as a priority group for flu vaccination. 14% of elderly received recommendation for flu vaccination from healthcare workers. Health communication, subsidy, and active role of healthcare workers are needed. Abstract: Background: The Chinese elderly face a significant threat from seasonal influenza, owing to the consistently low vaccination coverage. This study investigated the prevalence and determinants of influenza vaccination hesitancy among the Chinese elderly. Methods: In 2019, 3849 elderly individuals from 10 provinces in China were recruited in a cross-sectional survey. Multinomial logistic regression was applied to investigate the determinants of influenza vaccination hesitancy. Results: Among the elderly respondents, 37.18% expressed some degree of hesitancy towards influenza vaccination: 19.28% were hesitant, and 17.90% refused influenza vaccination, including 19.28% acceptors with doubts and 17.90% refusers. Only 39.10% of the respondents considered themselves as the priority group for influenza vaccination, and 13.93% reported receiving a recommendation for vaccination from healthcare workers. Respondents with higher education levels and from urban areas had significantly higher odds of vaccine hesitancy than their counterparts. Confidence in the safety of vaccines was negatively associated with vaccine hesitancy, but confidence in vaccine efficacy had no such association. Respondents who perceived themselves as highly susceptible to influenza (AOR = 0.85; 95 %CI = 0.77–0.93) and those aware of the elderly as a priority group for influenza vaccination (AOR = 0.51; 95 %CI = 0.41–0.64) had a significantly lower odds of being refusers. Conclusion: This study found a high prevalence of hesitancy towards influenza vaccination among the Chinese elderly, especially well-educated and urban-dwelling respondents. The government should address vaccine hesitancy through culturally appropriate communication, subsidies for vaccination, and actively promoting vaccines through primary care professionals.